Analisis Komparatif Bisnis Perusahaan Toyota di Jepang dengan Perusahaan Toyota di Indonesia: Analisis Komparatif Bisnis Perusahaan Toyota di Jepang dengan Perusahaan Toyota di Indonesia - dionisius sihombing; Rani Arfianty SS, M.Phil (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2024)
As a leading global automotive company, Toyota has been a successful representative in the unique history of the automotive industry. Its long history has marked the company's transformation from a small manufacturer to one of the largest players in the automotive industry. Central to Toyota's evolution is their ethical approach to business. adhere to quality, kaizen (continuous improvement), and commitment to customers, employees and society. The main pillar of Toyota's business ethics is awareness of the company's social and environmental responsibility, as well as contributing to society with sustainable CSR programs. Toyota's history is not just about technical innovation or global expansion, but also about how they combined business ethics with their success. At every step, strong business ethics have been the foundation of Toyota's long-term success, building trust with consumers, maintaining the company's reputation, and form a foundation in a competitive industry. further research, an in-depth exploration of the practical application of business values ​​in Toyota's strategy and success would be beneficial.